A Comparative In Vitro and In Vivo Study of Osteogenicity by Using Two Biomaterials and Two Human Mesenchymal Stem Cell Subtypes - Fievet, L.; Serratrice, N.; Brulin, B.; Giraudo, L.; Véran, J.; Degardin, N.; Sabatier, F.; Féron, F.; Layrolle, P. (Frontiers in Cell and Developmental Biology, 2022)
Background: Bone repair induced by stem cells and biomaterials may represent an alternative to autologous bone grafting. Mesenchymal stromal/stem cells (MSC), easily accessible in every human, are prototypical cells that can be tested, alone or with a biomaterial, for creating new osteocytes. The aim of this study was to compare the efficiency of two biomaterials - biphasic calcium phosphate (BCP) and bioactive glass (BG) - when loaded with either adult bone marrow mesenchymal stem cells (BM-MSC) or newborn nasal ecto-mesenchymal stem cells (NE-MSCs), the latter being collected for further repair of lip cleft-associated bone loss. Materials and methods: BM-MSCs were collected from two adults and NE-MSCs from two newborn infants. An in vitro study was performed in order to determine the best experimental conditions for adhesion, viability, proliferation and osteoblastic differentiation on BCP or BG granules. Bone-associated morphological changes and gene expression modifications were quantified using histological and molecular techniques. The in vivo study was based on the subcutaneous implantation in nude mice of the biomaterials, loaded or not with one of the two cell types. Eight weeks after, bone formation was assessed using histological and electron microscopy techniques. Results: Both cell types - BM-MSC and NE-MSC - display the typical stem cell surface markers - CD73+, CD90+, CD105+, nestin - and exhibit the MSC-associated osteogenic, chondrogenic and adipogenic multipotency. NE-MSCs produce less collagen and alkaline phosphatase than BM-MSCs. At the transcript level, NE-MSCs express more abundantly three genes coding for bone sialoprotein, osteocalcin and osteopontin while BM-MSCs produce extra copies of RunX2. BM-MSCs and NE-MSCs adhere and survive on BCP and BG. In vivo experiments reveal that bone formation is only observed with BM-MSCs transplanted on BCP biomaterial. Conclusions: Although belonging to the same superfamily of mesenchymal stem cells, BM-MSCs and OE-MSCs exhibit striking differences, in vitro and in vivo. For future clinical applications, the association of BM-MSCs with BCP biomaterial seems to be the most promising.